Do Wages Grow with Experience? Deciphering the Russian Puzzle - Eugenia Chernina; Vladimir Gimpelson (Institute of Labor Economics (IZA), 2022)
The study explores how wages grow with experience in the Russian Federation. In all available cross-sectional data, the trajectory of the observed wage–experience profile is flat, peaks early, and declines sharply afterwards. This shape looks puzzling since it differs starkly from that observed in both developed and developing countries. We show that a proper interpretation of the wage–experience profile is hindered by the APC problem, when the effects of time, cohort, and experience are mixed. Our study uses data from the RLMS-HSE household survey covering the years 2000-2019. Relying on human capital theory, we apply a procedure suggested by Heckman et al. (1998) and advanced in Lagakos et al. (2018) to disentangle the APC effects. With certain assumptions concerning human capital depreciation due to aging, our results show that Russian wages do grow monotonically with experience. However, this growth is partially offset by the cohort effect that that proceeds in the opposite direction, thus reflecting massive depreciation of the human capital of workers from older cohorts. Meanwhile, the time effect mirrors the general GDP path as well as all booms and busts over the period.
Keywords: J24; J31; 330; the human capital; wages; experience; wage–experience profile; Russia